2008
DOI: 10.1371/journal.pntd.0000290
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Schistosoma mansoni Adult Worms by Rhesus Macaques: Basis for a Therapeutic Vaccine?

Abstract: BackgroundAmong animal models of schistosomiasis, the rhesus macaque is unique in that an infection establishes but egg excretion rapidly diminishes, potentially due to loss of adult worms from the portal system via shunts or death by immune attack.Principal FindingsTo investigate this, six rhesus macaques were exposed to Schistosoma mansoni cercariae and the infection monitored until portal perfusion at 18 weeks. Despite a wide variation in worm numbers recovered, fecal egg output and circulating antigen leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
94
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(110 citation statements)
references
References 44 publications
8
94
0
Order By: Relevance
“…Similar to previous studies [14], in present experiments, IgE was also not detectable in vaccinated animals. As recorded in this study, early emergence with short lives of IgM responses and very low or undetectable levels of IgE were also observed in the “self-curing” S. mansoni -rhesus macaque model [41]. Cumulatively our data on Sm-p80 specific humoral responses indicate that a mixed Th1/Th2 type of priming was achieved following vaccination with Sm-p80-VR1020 vaccine.…”
Section: Discussionsupporting
confidence: 78%
“…Similar to previous studies [14], in present experiments, IgE was also not detectable in vaccinated animals. As recorded in this study, early emergence with short lives of IgM responses and very low or undetectable levels of IgE were also observed in the “self-curing” S. mansoni -rhesus macaque model [41]. Cumulatively our data on Sm-p80 specific humoral responses indicate that a mixed Th1/Th2 type of priming was achieved following vaccination with Sm-p80-VR1020 vaccine.…”
Section: Discussionsupporting
confidence: 78%
“…The antibodies specific for Sm-Cathepsin B may be performing a neutralizing task; thus, blocking nutrient uptake and leading to parasite starvation. Immunoproteomic studies concerning schistosomiasis self-cure in rhesus macaques revealed that gut digestive enzymes were common IgG targets in high responder animals [40]. This observation strengthens the potential role of Sm-Cathepsin B specific antibodies in protection.…”
Section: Discussionsupporting
confidence: 60%
“…Sera obtained from donor immunized mice and baboons have been shown to protect recipients against subsequent schistosome challenge when passively transferred (Byram et al 1979; Doenhoff et al 1979; Mangold and Dean 1986; Melo et al 2014; Torben et al 2011). Studies utilizing schistosome non- and/or semi-permissive host such as rats have shown that resistance to schistosome infections as well as mechanism of schistosome killing are almost entirely humoral mediated by high IgG antibodies (Knopf et al 1977; Wilson et al 2008). Our group have also demonstrated the potential effector role of antibody dependent complement mediated cytotoxicity (ADCC) in schistosome killing (Torben et al 2012).…”
Section: Discussionmentioning
confidence: 99%